2022
DOI: 10.1093/ejcts/ezac016
|View full text |Cite
|
Sign up to set email alerts
|

4D-flow cardiac magnetic resonance imaging after aortic root replacement with long-valved decellularized aortic homografts: comparison to valve-sparing aortic root replacement and healthy controls

Abstract: OBJECTIVES Long-valved decellularized aortic homografts (DAH) may be used in young patients to treat aortic valve disease associated with aortic root dilatation, thereby eliminating the need for prosthetic material and anticoagulation. METHODS Thirty-three male subjects in 3 equally sized cohorts were compared: patients following DAH implantation with a median age of 29 years [interquartile range (IQR) 27.5–37.5], patients po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Decellularized aortic homografts (DAH) have the potential to be less immunogenic [ 13 ] and early results have demonstrated significantly better freedom from adverse events than conventional cryopreserved aortic homografts. DAH results are comparable to those for Ross operations, achieving normal haemodynamics without the need to remove the pulmonary valve [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 93%
“…Decellularized aortic homografts (DAH) have the potential to be less immunogenic [ 13 ] and early results have demonstrated significantly better freedom from adverse events than conventional cryopreserved aortic homografts. DAH results are comparable to those for Ross operations, achieving normal haemodynamics without the need to remove the pulmonary valve [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 93%
“…Decellularized aortic homografts (DAH) may provide an additional AVR option for very young patients as they can potentially address the high failure rates of conventional allogenic and xenogeneic AVR prostheses [ 12 , 13 ]. The near-normal haemodynamics in combination with the ability to repair a malfunctioning aortic root are especially important for patients with impaired myocardial function and patients with multiple previous aortic valve procedures [ 14 ]. Recent studies, however, suggested that an immunological, antibody-mediated response is present in almost all patients, which appears to be highly individual in terms of intensity [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Decellularized homografts (DH) have been used since the early 2000s and have already shown good outcomes in younger patients with respect to survival and hemodynamic performance [14][15][16][17]. Compared to conventional homografts, different schemes of enzymatic and detergent removal of the donor cells are applied to reduce the immunogenicity of the homograft, potentially increasing the durability of the valve [18].…”
Section: Introductionmentioning
confidence: 99%